2020
DOI: 10.1371/journal.pone.0229224
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease from shingles and post-herpetic neuralgia in the over 80 year olds in the UK

Abstract: Background The current UK vaccination programme for herpes zoster (HZ) excludes people aged �80 years. This study aimed to quantify the number of individuals �80 years who missed HZ vaccination and the consequent epidemiological and economic burden of HZ and post-herpetic neuralgia (PHN). Methods Immunocompetent individuals aged �80 years between 1 st September 2013 and 31 st December 2017 in the Clinical Practice Research Datalink were selected and linked to Hospital Episodes Statistics, where available. Rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Regarding HZ vaccination, the positive impact on epidemiologic indicators has been seen in the reduction of HZ incidence in children vaccinated against varicella [ 28 ]. Some studies propose that this impact may be greater among the elderly with high coverage (currently between 58 and 72% of the population) [ 29 , 30 ]. In Spain, it is estimated that 97% of the child population is vaccinated against varicella, but in the elderly this coverage decreases to 57%.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding HZ vaccination, the positive impact on epidemiologic indicators has been seen in the reduction of HZ incidence in children vaccinated against varicella [ 28 ]. Some studies propose that this impact may be greater among the elderly with high coverage (currently between 58 and 72% of the population) [ 29 , 30 ]. In Spain, it is estimated that 97% of the child population is vaccinated against varicella, but in the elderly this coverage decreases to 57%.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this vaccine proved its efficacy in a pivotal randomized clinical trial by reducing the incidence of HZ and PHN by 51% and 67% respectively [10]. More recent studies have demonstrated higher vaccine effectiveness against incident HZ and PHN [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[3] As the sequelae neuralgia usually lasts from a few months to half a year, it will seriously affect the patient's daily life and work. [4] Research also shows that 45% of patients have symptoms such as anxiety, depression, and lack of concentration. [5] Modern medicine believes that the pathogenesis of PHN mainly includes peripheral nerve and central nerve pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant survey statistics, the incidence of shingles is about 10% to 19%, which is even higher for the elderly [3] . As the sequelae neuralgia usually lasts from a few months to half a year, it will seriously affect the patient's daily life and work [4] . Research also shows that 45% of patients have symptoms such as anxiety, depression, and lack of concentration [5] …”
Section: Introductionmentioning
confidence: 99%